The Painting "Jamuan Kerinduan" by Nurali, a Regional Artist Who also Enlivens Contemporary Art in Indonesia - Risa Septyana; Tantra Sakre (IMAGIONARY, 2022)
This writing is motivated by the art world today, that contemporary art is an art movement that gives freedom to art connoisseurs and art creators in creating works and assessing beautiful art. Independence which gives freedom to work, both in terms of: concept of work, ideas, visual/visual forms, techniques, character of visual language, freedom of expression, and other freedoms. The purpose of this paper is to find out the results of the analysis of visual forms in contemporary paintings. Where the discussion is focused on the artist Nurali and examines one of his paintings entitled "Jamuan Kerinduan". The results obtained in writing are to examine the visual analysis of the painting using art science and the principles of contemporary art. The conclusion is the result of an analysis by using art science on the principles of contemporary art, the painting "Jamuan Kerinduan" by Nurali and that work, entered into contemporary art which has the freedom to work, both freedom in images/visuals, techniques, concept and so on. Has distinctive features and characteristics according to the concept of its creator. The depiction of marginal creatures/figures, the hallmark of Nurali's depiction is the depiction of humans, which becomes the concept of the work that comes from an understanding of the surrounding environment.